Keterampilan Statistika dan Data Science: Manfaatnya di Berbagai Bidang pada Era Digital - Alfian Futuhul Hadi; Halimatus Sa'diyah (Abdimas Universal, 2022)
Data Scientist is a trending career in recent years. The survey results show that the need for a data scientist is high, but the availability is very low with limited capabilities. A data scientist needs statistics and programming skills. But, from a student's point of view, statistics is considered the same as mathematics, so it is less desirable because it is mathematical and is considered difficult. Students as prospective workers need to have insight into how to work and skills in the era of the industrial revolution 4.0. Failure to adapt to this new era will lead to increased unemployment of working age in the future. It is important to make the younger generation understand about statistics and data science skills, including the opportunities and job that exist, so efforts are needed to disseminate them. It is hoped that after understanding it, the younger generation will be interested in choosing a profession related to digital. The target audience is students of SMAN 3 Jember. The method used is presentation, then evaluation using a questionnaire. More than 79% of students rated the material presented as important, interesting and up to date. Students can also understand most of the material given, and the level of student interest in both fields is very high. This activity was generally successful.